2021
DOI: 10.1159/000517426
|View full text |Cite
|
Sign up to set email alerts
|

Age as an Independent Predictor of Adult Spinal Cord Stimulation Pain Outcomes

Abstract: <b><i>Introduction:</i></b> Spinal cord stimulation (SCS) is an efficacious chronic pain treatment most commonly used in middle-aged patients. Results from previous studies that investigated SCS′ effects in older patient populations have been equivocal. We examine whether SCS outcomes correlate with age. <b><i>Methods:</i></b> We retrospectively examined prospectively collected outcomes from 189 patients who underwent SCS at Albany Medical Center between 2012 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Figure 1 depicts the PRISMA flow chart of the study selection and inclusion process. A total of 36 studies met the inclusion criteria and were included for the qualitative analysis 22 40–74 Table 1. describes the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 1 depicts the PRISMA flow chart of the study selection and inclusion process. A total of 36 studies met the inclusion criteria and were included for the qualitative analysis 22 40–74 Table 1. describes the characteristics of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…describes the characteristics of the included studies. There were 7 included RCTs,22 40 50 55 61 63 69 17 prospective studies,41–44 46 47 51 56 59 60 62 64 65 68 70–72 11 retrospective studies,45 48 49 52–54 57 58 66 67 73 and 1 ambispective observational study 74. Thirteen studies were conducted in multiple centers 41–43 46 51 55 56 61 63 68 69 72–74.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relatively few studies have explored the differences in long-term outcomes based on patient’s age, sex or gender. Retrospective observational studies indicate that younger age is associated with increased conversion to full implant25 and increased age was a predictor of higher explantation risk,33 although a recent small study found no difference in pain scores with age 67. Women have been noted to have a higher rate of explantation, mostly because of device-related discomfort,68 and men with refractory angina pectoris who are treated with SCS have been noted to have a larger improvement in quality of life compared with women with SCS for refractory angina 34.…”
Section: Committee Statements and Recommendationsmentioning
confidence: 99%